Rural Depopulation in the Pampean Region of Argentina: Intervention Model - Stratta Fernández, Ricardo (2013)
The depth of technological changes in the Pampas agriculture, led to the downsizing of the agricultural structure, due to the loss of producers and the decline of the population in rural areas. This article analyses this problem, and proposes a new intervention model for rural communities, incorporating the conceptual foundations of WWP (Working With People), the planning as a way of Social Learning and elements of the European initiative LEADER. In addition to the development of these principles, their application in Punta Indio and the Pampas region of Argentina is described. After a number of years since it began, its importance in articulating rural development in rural communities with depopulation problems is also highlighted.